2022
DOI: 10.2196/41482
|View full text |Cite
|
Sign up to set email alerts
|

Development of the First Episode Digital Monitoring mHealth Intervention for People With Early Psychosis: Qualitative Interview Study With Clinicians

Abstract: Background Mobile health (mHealth) technologies have been used extensively in psychosis research. In contrast, their integration into real-world clinical care has been limited despite the broad availability of smartphone-based apps targeting mental health care. Most apps developed for treatment of individuals with psychosis have focused primarily on encouraging self-management skills of patients via practicing cognitive behavioral techniques learned during face-to-face clinical sessions (eg, challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Furthermore, they argue that joint reflection by the clinician and patient should be used to address SDM-related risks ( 40 ). Also (online/mobile) health interventions are developed to improve SDM ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they argue that joint reflection by the clinician and patient should be used to address SDM-related risks ( 40 ). Also (online/mobile) health interventions are developed to improve SDM ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Congruent with other trends in the literature [ 23 ], patient feedback and higher rates of fidelity and feasibility in the modular version of the DMHI suggest that a structured approach may maximize acceptability, adoption, appropriateness, fidelity, and feasibility. In addition, findings from a recent qualitative study gathering clinician feedback on another DMHI suggested that adaptable DMHIs may work to improve implementation outcomes such as feasibility, appropriateness, adoption, and penetration [ 24 ]. Prior research using smartphone apps in the care of patients with early psychosis has also shown feasibility [ 9 , 25 ], which is similar to our results; however, the use of digital navigators in this study is novel.…”
Section: Discussionmentioning
confidence: 99%